PERTANGGUNGJAWABAN PIDANA KORPORASI TERHADAP LIMBAH PRODUKSI DALAM PERSPEKTIF TINDAK PIDANA LINGKUNGAN HIDUP (Studi Putusan Nomor: 5054 K/Pid.Sus-LH/2022) - Mustariyanto, Wahyu; Lutfianidha, Redyana; Maryuliyanto, Maryuliyanto; Putri, Fitria (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research discusses: "CORPORATE CRIMINAL LIABILITY FOR PRODUCTION WASTE FROM THE PERSPECTIVE OF ENVIRONMENTAL CRIMES (Study of Decision Number: 5054 K/Pid.Sus- LH/2022)". This study presents two main problems, namely: 1. How is the criminal liability of corporations and corporate managers in Decision Number 5054 K/Pid.Sus-LH/2022 based on the principle of strict liability and the principle of vicarious liability?, 2. How is the urgency of strengthening criminal liability for managers or leaders in corporations, in order to create a deterrent effect and prevent environmental crimes from occurring? The objectives of the study are: 1. To determine the criminal liability of corporations and corporate managers in Decision Number 5054 K/Pid.Sus- LH/2022 related to environmental pollution crimes through the approach of the principle of strict liability and the principle of vicarious liability. 2. To examine the urgency of strengthening criminal liability for managers or leaders in corporations in order to create a deterrent effect, increase legal compliance, and prevent the recurrence of criminal acts of pollution or environmental destruction by business entities in the future. This study uses a normative juridical research approach with the specifications of the statutory approach, conceptual approach, and case approach. The results of the study show that: 1. In Decision Number 5054 K / Pid.Sus-LH / 2022 there is a lack of law enforcement in the use of articles already available in the Environmental Protection and Management Law Number 32 of 2009 where Article 116 paragraph 1 point b and Article 116 paragraph 2 and Article 117 are not used in the decision. then the Supreme Court only uses the principle of strict liability to ensnare the corporation (PT. SASS) as the perpetrator of environmental crimes. Meanwhile, the managers or leaders of corporations who give orders or lead activities are not held criminally responsible even though it is regulated in Article 116 paragraph 1 point b and Article 116 paragraph 2 and Article 117 which are not used in the decision. 2. By combining the principles of strict liability (against corporations) and the principle of vicarious liability (against managers), it is very important that law enforcers should conduct a comprehensive evaluation and consider the use of the provisions of the articles and principles as a legal basis in every decision. Ignoring the use of Article 116 paragraph (1) letter b, Article 116 paragraph (2), and Article 117 of Law Number 32 of 2009 on Environmental Protection and Management, along with the principle of vicarious liability, has the potential to result in an absence of a deterrent effect on the individuals involved, considering that criminal responsibility is not only attached to the corporation, but also to the leaders who give orders. This condition will ultimately have an impact on suboptimal protection of the public interest and environmental sustainability.